Labor unions, partisan coalitions and market reforms in Latin America - Murillo, Maria Victoria, 1967- (Cambridge studies in comparative politics., 2001)
"Due to economic crises, labor parties followed economic policies that hurt labor unions during the 1990s, such as trade liberalization and privatization. This book explains why labor unions resisted on some occasions and submitted on others and what the consequences of their actions were by studying three countries: Argentina, Mexico, and Venezuela. The comparison between the experiences of the three countries and five different sectors in each country shows the importance of politics in explaining labor reactions and their effects on economic policies."--Jacket